Possible Traces of Early Malay Settlement in South Sulawesi. Issue 147 (4th May 2022) - Hadrawi, Muhlis; Agus, Nuraidar; Hasanuddin
ABSTRACT: Indigenous written sources and local tradition attribute the emergence of the Bugis kingdom of Suppa on the west coast of South Sulawesi (Indonesia) to events in the 15th century. A founding female figure emerged from the sea with her entourage and, together with a 'descended' male figure, established the various kingdoms in the Ajattappareng area. Details in the story and persistent memory suggest the presence of Malays from Melaka. Given the nature and purposes of Bugis historiography and ideology, together with generalised support from archaeology, it seems that this may represent a valid memory of actual events.